Multiwalled carbon nanotubes-encapsulated gellan gum membrane for micro-solid phase extraction of selected polycyclic aromatic hydrocarbons in environmental water and beverages - Zulkipli, Nurul Aryani; Wan Mohd Khalik, Wan Mohd Afiq; Mohd Ariffin, Marinah; Aboul-Enein, Hassan Y.; Yahaya, Noorfatimah; Kamaruzaman, Sazlinda; Loh, Saw Hong (Springer, 2022)
Non-biodegradable plastics are an unresolved issue in solid waste management as recycling them is expensive. This study focused on formulating a biodegradable gellan gum (GG) membrane embedded with multiwalled carbon nanotubes (MWCNTs) as the adsorbent in the micro-solid phase extraction (µ-SPE) of selected polycyclic aromatic hydrocarbons (PAHs), i.e. phenanthrene, fluoranthene, pyrene and benzo[a]pyrene, in environmental water and fruit-juice beverage samples. PAHs quantitation was performed using micro-high-performance liquid chromatography coupled with ultraviolet detection. The MWCNTs GG membrane was fabricated by mixing MWCNTs in a hot GG solution, which was then crosslinked with glutaraldehyde to resist membrane swelling during extraction. Under the optimal extraction conditions, the proposed µ-SPE technique demonstrated good linearity (1–500 µg L−1; correlation coefficient of ≥ 0.9925) and ultra-trace detection limits (10–60 ng L−1). Good relative recoveries in the range of 81.3–114.9% with acceptable relative standard deviations (≤ 9.7%) revealed that matrix effects were insignificant because the MWCNTs-GG membrane-based µ-SPE offered a clean extract in these real samples. The proposed µ-SPE technique is proven to be sensitive, accurate and green with an analytical eco-scale score of 81, which supports green analysis for a better tomorrow.